2016
DOI: 10.3390/rs8040301
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Mapping of Black Rock Coatings Using Hyperion Images: Sudbury, Ontario, Canada

Abstract: Base metal smelting activities can produce acidic rain that promotes vegetation loss and the development of black coatings on bedrock. Such coatings can form over large areas and are among the most prominent long-term vestiges of past smelting activities. In this study, multispectral images derived from Hyperion reflectance data were evaluated with regard to their utility in the discrimination and mapping of black rock coatings near Sudbury. Spectral angle mapper (SAM) classifications generated on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 73 publications
(97 reference statements)
1
9
0
Order By: Relevance
“…Notable associated absorption features were identified and were related to the mineralogical and elemental components of coatings. Comparisons between Rouyn-Noranda spectra and those previously collected in the Sudbury region were performed in order to determine if notable differences exist between the reflectance properties of coatings produced by emissions from the Horne smelter and those of coatings produced in the Sudbury region by the Falconbridge, Coniston, and Copper Cliff smelters 11 , 12 .…”
Section: The Rouyn-noranda Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…Notable associated absorption features were identified and were related to the mineralogical and elemental components of coatings. Comparisons between Rouyn-Noranda spectra and those previously collected in the Sudbury region were performed in order to determine if notable differences exist between the reflectance properties of coatings produced by emissions from the Horne smelter and those of coatings produced in the Sudbury region by the Falconbridge, Coniston, and Copper Cliff smelters 11 , 12 .…”
Section: The Rouyn-noranda Study Areamentioning
confidence: 99%
“…Prior research demonstrated the effectiveness of the maximum likelihood algorithm in the remote-sensing-based identification of coated rock surfaces in the Sudbury region of Ontario, Canada 11 , 12 . In that work, the maximum likelihood algorithm, with null class implemented, outperformed a feedforward backpropagation neural network classifier and the Spectral Angle Mapper classifier by consistently producing useful and representative coating maps characterized by low proportions of false positives.…”
Section: The Rouyn-noranda Study Areamentioning
confidence: 99%
See 3 more Smart Citations